2006
DOI: 10.1200/jco.2005.04.8397
|View full text |Cite
|
Sign up to set email alerts
|

ErbB-3 Predicts Survival in Ovarian Cancer

Abstract: HER3 may represent a new prognostic factor in primary epithelial ovarian cancer. Pending validation, exploration of therapeutic strategies to block HER3 could be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(136 citation statements)
references
References 33 publications
3
133
0
Order By: Relevance
“…237 It has recently been confirmed that high ERBB3 expression in ovarian cancer correlates with poor survival. 246 In the latter immuno-histochemical study, ERBB3 overexpression was more common than high ERBB2 and the predominant localization of the ERBB3 protein was cytoplasmic, in contrast to the typical membrane staining for ERBB2.…”
Section: Ovarian Cancermentioning
confidence: 82%
“…237 It has recently been confirmed that high ERBB3 expression in ovarian cancer correlates with poor survival. 246 In the latter immuno-histochemical study, ERBB3 overexpression was more common than high ERBB2 and the predominant localization of the ERBB3 protein was cytoplasmic, in contrast to the typical membrane staining for ERBB2.…”
Section: Ovarian Cancermentioning
confidence: 82%
“…Furthermore, only few studies have described the tissue expression of the HER3 and HER4 receptor protein in ovarian cancer. The HER3 receptor is present in the majority of malignant ovarian tumors (10)(11)(12)(13) and one study (14) has also reported that high HER3 expression is a poor prognostic factor in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…ErbB-3 is highly expressed in many human tumor types and has been variably associated with poor prognosis (Yi et al, 1997;Tanner et al, 2006;Reschke et al, 2008). Moreover, recent studies suggest that breast cancers exposed to ErbB-1 or ErbB-2 targeted therapies escape this inhibition by persistent activation of ErbB-3 and the PI3-K-Akt pathways (Baselga and Swain 2009), suggesting that agents targeting ErbB-3 could provide a novel and promising approach toward the treatment of some cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This resistance is often associated with compensation by or upregulation of other ErbB family members such as ErbB-3 and ErbB-4 (Bianchi et al, 2006;Engelman et al, 2007;Karamouzis et al, 2007) or increased production of ErbB-1 or ErbB-3 ligands by tumor cells (Ishikawa et al, 2005;Zhou et al, 2006). ErbB-3 overexpression has been documented in breast, ovarian and lung cancer and this genetic feature has been correlated with poor prognosis (Yi et al, 1997;Witton et al, 2003;Tanner et al, 2006). On activation by heregulins, ErbB-3 dimerizes with ErbB-2 and ErbB-1 to generate potent oncogenic receptor heterodimers (Alimandi et al, 1995;Wallasch et al, 1995).…”
Section: Introductionmentioning
confidence: 99%